Consumer Protection Against Final Decisions of the Consumer Dispute Settlement Body is a Quasi-Court - Harahap, Pardamean; Sulaiman, Abdullah (Journal of Social Research, 2023)
The position of the Consumer Dispute Settlement Body in the judicial power law is not as a court institution but carries out an adjudicating function called a Quasi Court with resolution through mediation, conciliation, and arbitration, the decisions of which are final and binding.  The formulation of the problem in this paper is: Why is legal protection needed for consumers as a Quasi Court from the Final Decision of the Consumer Dispute Settlement Agency (BPSK)? Meanwhile, the method used in this research is the normative method, using a statutory and analytical approach, then the legal materials used are primary, secondary, and tertiary legal materials.  Consumers are weaker in existence than business actors, because business actors often carry out actions that can harm consumers to gain profits, therefore consumers need to receive legal protection, even though UUPK has been formed to resolve disputes through the Consumer Dispute Resolution Agency (BPSK), but the BPSK decision which is final and binding has not been fully implemented consistently as stated in the Consumer Protection Law (UUPK), because there is still an opportunity to submit objections for parties who object to the BPSK decision.